Avaliação e monitoramento da obesidade em adultos residentes do município de Rio Claro - SP - Goulardins, Guilherme Stefano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Obesity is characterized by an excess of fat on the body and can results several problems on the individual health. As an epidemic of modern times, the prevalence started to increase at an accelerated rate from the 90's in worldwide. Data on the epidemic in Brazil and medium-sized cities are scarce, and the monitoring of obesity is essential for development public policy. So, the objective was to analyze the individual factors associated with obesity such as age, gender, education, marital status, economic class and level of physical activity and make a monitoring of obesity in adults in the city of Rio Claro - SP. To do this, the survey was conducted longitudinally, consists of two times at an interval of seven years. At first (2008) were interviewed 1588 adults in the city of Rio Claro distributed throughout the city. At the second phase (2014/2015) was conducted a new interview with the same subject in 1588. In 2008, personal information collected and applied some questionnaires with the physical activity level, food intake and quality of life. To assess obesity in adults was calculated the body mass index (BMI) proposed by the World Health Organization (WHO) from the high reported weight and height. For older people it used a specific BMI. The prevalence was used percentages and their respective confidence intervals of 95%. For the incidence, was calculated by the formula of cumulative incidence, both stratified by personal characteristics (gender, economic class, education, marital status and age). Thus it was observed that there was an increase in the prevalence of obesity in 2008 (19.0%), increasing to 26.7% in 2015. The cumulative incidence was 14.4% in the range of 7 years. As for the groups, we observed a significant difference between economic class and obesity being less prevalent among people of class D / E. Regarding marital status, it was observed that married / cohabiting have a higher prevalence. Therefore, we can conclude...

A obesidade é caracterizada por um excesso de gordura pela extensão total do corpo e pode acarretar em vários problemas na saúde do indivíduo. Considerada uma epidemia dos tempos modernos, sua prevalência mundial passou a aumentar em um ritmo acelerado a partir da década de 90. Dados sobre essa epidemia no Brasil e em cidades de médio porte são escassos, sendo que o monitoramento da obesidade é essencial para a elaboração de políticas públicas. O objetivo foi analisar os fatores individuais associados à obesidade como idade, gênero, escolaridade, estado civil, classe econômica e nível de atividade física e realizar o monitoramento da obesidade em adultos no município de Rio Claro - SP. Para tal, a pesquisa foi realizada de forma longitudinal, constituída por dois momentos em um intervalo de sete anos. No primeiro momento (2008) foram entrevistados 1588 adultos no município de Rio Claro distribuídos por todo o município e no segundo momento (2014/2015) foi realizado uma nova entrevista com os mesmos 1588 sujeitos. Foram coletadas informações pessoais e aplicado alguns questionários sobre nível de atividade física, alimentação e qualidade de vida. Para avaliar a obesidade nos adultos foi calculado o Índice de Massa Corporal (IMC) proposto pela Organização Mundial de Saúde (OMS) a partir do peso e estatura altos relatados. Para os idosos se utilizou uma fórmula de IMC específico para essa faixa etária. Para a prevalência foi utilizado porcentagens e seus respectivos intervalos de confiança de 95% e a incidência foi calculada pela fórmula da incidência cumulativa, ambas estratificadas pelas características pessoais (sexo, classe econômica, escolaridade, estado civil e idade). Com isso foi possível observar que houve um aumento na prevalência de obesidade que em 2008 era de 19% passando para 26,7% em 2015. A incidência cumulativa foi de 14,4% no intervalo de 7 anos. Quanto aos grupos, foi observado uma...
Keywords: Educação fisica; Obesidade; Qualidade de vida; Exercício físico; Rio Claro (SP)